The Effectiveness of Ji Chang Wook as Traveloka's Brand Ambassador Among Millennials in Indonesia - Isyela Netanya Putri Lantu; Daniel Budiana; Astri Yogatama (Journal of Content and Engagement, 2025)
This study aims to measure the effectiveness of Ji Chang Wook as Traveloka's brand ambassador among Millennials in Indonesia. The research uses a descriptive method with a quantitative approach. Data were collected through an online survey using a questionnaire as the data collection tool. The respondents were 100 Millennials who met the following criteria: they were familiar with Traveloka and Ji Chang Wook as the brand ambassador, and had used Traveloka's services. The effectiveness of the brand ambassador was measured using the VisCAP indicators, which include visibility, credibility, attraction, and power. The results showed an effectiveness score of 4.33, with the attraction indicator recording the highest score of 4.44. In this indicator, respondents believed that Ji Chang Wook is a visually appealing brand ambassador with engaging message delivery characteristics. As a result, most female respondents were drawn to Ji Chang Wook's visual appeal, while male respondents were more attracted to his engaging personality. These findings indicate that Ji Chang Wook has successfully built a strong appeal among Millennials as Traveloka's consumers, while also strengthening the positive perception of the brand. This study highlights the importance of selecting a relevant brand ambassador with strong appeal to enhance emotional connections and consumer engagement with the brand.